Pengetahuan Gizi Remaja SMPN 40 Kota Bandung - Darmawati, Irma; Arumiyati, Sela (UPPM Politeknik Kesehatan Kemenkes Ternate, Maluku Utara, Indonesia, 2017)
Nutritional knowledge can determine the nutritional status and the behavior of teenagers in choosing food. The increase in the prevalence of nutritional problems in Indonesia are not only limited to less nutritional problems but has also increased to the double burden of malnutrition. The prevalence of nutritional problems is more on teen aged 13-15 years in Indonesia amounted to 10.8%, comprising 8.3% 2.5% overweight and obesity. Research was conducted to find out the description of the nutritional knowledge owned by teens by using descriptive method which aims to know the description of knowledge about adolescent nutritional status in 40 SMP Bandung. The number of samples obtained as many as 89 people using Proportional Random Sampling techniques. Analysis of the frequency distribution is done through knowledge. Research results shows 40 adolescents knowledgeable good 48 people (53.9%), just 22 people (24.7%), lack of 19 people (21.3%), with the highest points are obtained on a category of obesity about 81 people (91.0%). The lowest points are obtained on the category how to measure the nutritional status about 53 people (59.6%). The school is expected to pay more attention to and provide education about knowledge of nutrition and nutritional status. For the ministry of health expected more frequent monitoring and coaching the UKS and PMR on the school.